Challenges of healthcare financing in the world’s largest refugee camp: a mixed-method study among healthcare stakeholders for Rohingya refugees in Bangladesh - Isabel Smith; Imdadul Haque Talukdar; Sayeeda Tarannum; M A Rifat; Priyanka Boga; Jubayer Mumin; Pablo André Veronés; Ziba Mahdi; Syeda Saima Alam; Arif Faysal Khan (BMJ Open)
Objectives This study aimed to increase the understanding of healthcare stakeholders’ viewpoints on the challenges and potential solutions regarding healthcare financing for the Rohingya refugees in Cox’s Bazar.Design A mixed-method approach, containing semi-structured interviews with healthcare stakeholders and review of financial documents, was employed. Thematic analysis was performed to analyse the transcripts. Financial documents (available online) and reports from respective coordinating agencies were also reviewed.Setting Online key informant interviews (KIIs) were conducted from Stockholm with participants residing in Bangladesh between June 2022 and September 2022.Participants Eight KIIs were conducted with professional health programme managers, executives and personnel involved in policy coordination and implementation in refugee camps in Cox’s Bazar district of Bangladesh.Results We identified four themes and three subthemes outlining key challenges in healthcare funding, including decreasing funds (supported by a quantitative assessment) due to macroglobal issues, conflicting short-term and long-term priorities between implementing partners, insufficient efficacy due to challenges with collaborative priority-setting and implementing common processes, and a lack of consensus regarding equity between host and refugee communities.Conclusions The study identified unique challenges beyond the commonly discussed health financing issues in a resource-deficient setting: stakeholders’ conflicting priorities regarding funding and undecided equity issues among the host and refugee communities are worth scholarly and policy focus. A needs-based, equitable and effective action plan might ensure the proper utilisation of resources.